PENGARUH PENERAPAN SISTEM E-FILLING DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SANKSI PAJAK SEBAGAI VARIABEL PEMODERASI - Prayoga, Gilang Bagus; Selfiani, Selfiani; Surya, Patricia Kartika; Lumbantobing, Sabar Pardamean (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
The government implements a tax collection system based on self-assessment or known as A system for self-evaluation. The system for self-evaluation is a system where It is trusted that taxpayers will compute and submit their own taxes owed by Taxpayers, while the tax officers themselves are tasked with supervising it. This implies that the accomplishment or inability of this system is largely decided by the compliance of Taxpayers and optimal supervision from the tax authorities themselves (Utrimi, 2021). In order to ascertain how the e-filing system's adoption has affected taxpayer compliance, To ascertain how tax knowledge affects taxpayer compliance, to evaluate and assess the impact of taxes sanctions moderating the connection between compliance of taxpayers and the adoption of electronic filing, In order to examine and assess how tax penalties affect the connection between the taxpayer and compliance and tax knowledge, to ascertain how tax penalties affect compliance of taxpayers. This research approach makes use of numerical data and primary data, the sample used is respondents in the central LPP TVRI environment. 110 respondents make up the sample size, and the data technique makes use of SPSS software version 25. Descriptive statistics, validity testing, and reliability are the methods of analysis that are employed. testing, hypothesis testing. Research results The LPP TVRI office's there is no impact on taxpayer compliance. by the presence of e-filing; taxpayer compliance is impacted by tax knowledge; the connection between electronic filing implementation as well as taxpayer adherence is weakened by tax penalties; the connection between tax knowledge and taxpayer compliance at the LPP TVRI office is strengthened by tax sanctions; and taxpayer knowledge at the LPP TVRI office is not impacted by tax penalties.